Closing the digital divide in education: an innovative review of demand and supply side policies in four ASEAN member states - McFarlane, Daniel; Mieruch, Yannik; Wann Si, Nang Lao (International Journal of Evaluation and Research in Education (IJERE), 2024)
The rapid adoption of digital technologies in education highlights the importance of closing the digital divide in education. However, research on school connectivity policy regimes to bridge the digital divide in education in the Association of Southeast Asian Nations (ASEAN) region is lacking. The authors conducted a systematic review of policies in Cambodia, Malaysia, Thailand, and the Philippines following a framework synthesis approach. Through desk research, data was identified based on a supply and demand side framework and included policy documents from relevant ministries and departments, reports by international development organizations and non-governmental organizations, and academic literature. The analysis reveals an imbalance between supply and demand-side policies and regulatory approaches with governments in the analyzed countries favoring demand side policies.